Adenyl cyclase and interleukin 6 are downstream effectors of parathyroid hormone resulting in stimulation of bone resorption. - Greenfield, E M; Shaw, S M; Gornik, S A; Banks, M A (The Journal of Clinical Investigation, 1995)
Parathyroid hormone and other bone resorptive agents function, at least in part, by inducing osteoblasts to secrete cytokines that stimulate both differentiation and resorptive activity of osteoclasts. We previously identified two potentially important cytokines by demonstrating that parathyroid hormone induces expression by osteoblasts of IL-6 and leukemia inhibitory factor without affecting levels of 14 other cytokines. Although parathyroid hormone activates multiple signal transduction pathways, induction of IL-6 and leukemia inhibitory factor is dependent on activation of adenyl cyclase. This study demonstrates that adenyl cyclase is also required for stimulation of osteoclast activity in cultures containing osteoclasts from rat long bones and UMR106-01 rat osteoblast-like osteosarcoma cells. Since the stimulation by parathyroid hormone of both cytokine production and bone resorption depends on the same signal transduction pathway, we hypothesized that IL-6 might be a downstream effector of parathyroid hormone. We found that addition of exogenous IL-6 mimics the ability of parathyroid hormone to stimulate bone resorption. More importantly, an antibody directed against the IL-6 receptor blocks moderate stimulation of osteoclast activity induced by the hormone. Interestingly, strong stimulation of resorption overcomes this dependence on IL-6. Thus, parathyroid hormone likely induces multiple, redundant cytokines that can overcome the IL-6 requirement associated with moderate stimulation. Taken together with studies showing that many other bone resorptive agents also stimulate IL-6 production, our results suggest that IL-6 may be a downstream effector of these agents as well as of parathyroid hormone. Images